THE EFFECTIVENESS OF BEHAVIORAL COUNSELING SERVICES WITH SELF MANAGEMENT TECHNIQUES TO REDUCE AGGRESSIVE BEHAVIOR - Azmi, Khilman Rofi (Universitas PGRI Semarang, 2022)
This study aims to determine how effective behavioral counseling services with self-management techniques are to reduce aggressive behavior. In this study using a population of 33 students, from the population the researchers took a sample of 8 students. This research technique uses a sampling technique in the form of non-probability sampling with purposive sampling. Purposive Sampling technique is a sampling technique with certain considerations. This research is a quantitative research in the form of Pre Experimental with pre test and post test research designs. The results of this study indicate that behavioral counseling services are very effective in reducing aggressive behavior, this can be seen from the values of the pre test (before being given treatment) and post test (after being given treatment). for the pre-test value of 167. 62 and post-test of 125.88, it means that from this value there is a decrease so that behavioral counseling services can be said to be effective. The Paired Sample T-test can strengthen the pre-test and post-test scores, for the t-count value is 23.857 and the t-table is 2.365. So it can be concluded that Ho is rejected and Ha is accepted (23,857 2,365). Thus, behavioral counseling services are effectively used to reduce aggressive behavior.